Diabetic Nephropathy: Disease Burden, Pathophysiology and Therapeutic Approaches - Kabir, Md Anwarul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2023; 41: 5-6